The position of environmental law in Malaysia in dealing with domestic and regional air pollution problems - Mustafa, Maizatun; Rusli, Mohd Hazmi (Kolej Universiti Islam Antarabangsa Selangor ( KUIS ), 2016)
For Malaysia, the increasing concentration of people and economic activities in urban and sub-urban areas, as well as the growing numbers of agricultural areas, industries and vehicle fleet have contributed to the problem of air pollution in the country. Since sources of air pollution are varied, different legal approaches are required to regulate and control various sources of air pollution. The main objectives of this paper are to lay down existing law applicable to protect air quality from various pollution sources, and to highlight one type of air pollution problem faced by Malaysia annually, namely that of transboundary haze pollution. Compared with other sources of air pollution, the control of haze is more complicated as it can originate both domestically and from abroad. If such haze derived beyond Malaysia’s boundary, international efforts would then be required to regulate it. For this reason, the paper seeks to identify the position of law in Malaysia in controlling haze across border and to identify gaps in the law that require improvement.